Rabam Jawa: transcultural performance and aesthetic transformation of Javanese identity in Thai Dance - Prakasiwi, Galih; Sasongkroh, Navee; Nurvijayanto, Ribeth (Gelar: Jurnal Seni Budaya, 2025)
This research investigates Rabam Jawa (ระบำชวา) as a case to show a complex case of cultural representation blending Java and Thai culture. It is not just a replication of Javanese dance, but such an act of cultural appropriation and aesthetic transformation where a Thai mode of Javanese-imaginary is constructed. The study integrates Maruska Svasek’s theory of cultural transit and Julie Sander’s concept of appropriation that employs a qualitative and interpretive analysis. Through Svasek and Sanders, this research analyzes how cultural product is not just transferred into another style, but actively recreated, which enriches the aesthetic paradigm of cross-cultural identity. The primary fieldwork was started in 2016 through interviews with senior dancers and a Thai national artist, and focus group discussions with teachers from Lopburi, Angtong, and Suphanburi College of Dramatic Art. This data was supplemented by ongoing choreographic observation and literature studies. The findings reveal the aesthetic domestication of Javanese performing elements (movement, music, and costume), mixed and transformed into Thai performance. This research contributes to transcultural performance studies by showing how Thai culture appropriates and styles foreign elements.